Questioning Urban Design Dimensions of the Cul-De-Sacs in the Walled City of Famagusta - Afşin, Nesil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
“Cul-de-Sac” is a french term that means the street pattern which have passage from one side and connects with larger streets. The other name of the “cul-de-sac” is Dead End Street. There are two different types of dead end streets, which are traditional and modern cul-de-sacs. According to the case study of this thesis, traditional cul-de-sacs’ typology will be refered. In the traditional urban texture, cul-de-sac is semi-public space that provides safety for children and semi-private space for adults. This typology brings significance to the urban pattern with the traces of traditional culture. As the aim of this thesis, ten cul-de-sacs situated in the Walled City of Famagusta are analised according to the six dimensions of urban design. These dimensions are visual, temporal, functional, social, morphological and perceptual dimensions. In this thesis, four chapters are included that are structured with introduction, literature review, case study that is the cul-de-sacs in the Walled City of Famagusta and conclusion. At the end of the study, the findings that determined throughout the thesis are presented and reccomondations are provided as a guide for further research. In this study, it is mainly determined that most of the cul-de-sacs are weak. In terms of physical and functional qualities. Keywords: Cul-de-sac (Dead End Street), Functional Dimension, Morphological Dimension, Urban Design, Perceptual Dimension, Physical Dimension, Social Dimension, Street Typology, Visual Dimension, Walled City of Famagusta

ÖZ : “Cul-de-sac”, tek taraflı geçişi olan ve diğer sokaklara bağlanan sokak dokusu anlamına gelmektedir. Fransızca kökenli olan bu terim, çıkmaz sokak anlamındadır. Çıkmaz sokaklar, geneleneksel ve modern olarak ikiye ayrılmaktadırlar. Bu tezde ele alınan çıkmaz sokak örneklerinin bulunduğu tarihi dokudan dolayı, geleneksel çıkmaz sokak dokularına değinmektedir. Geleneksel çıkmaz sokak örneklerine bakıldığında, bu sokaklar çocuklar için güvenli ve yetişkinler için yarı özel alan niteliği taşımaktadırlar. Bu sokak tipolojisi, gelenekselleşmiş kültürün izlerinin önemini vurgulamaktadır. Bu araştırmada, Gazimağusa Suriçinde bulunan çıkmaz sokakların görsel, fiziksel, fonksiyonel, sosyal, morfolojik ve algısal boyutlarını literatür taramasına bağlı kalarak değerlendirilmesi amaçlanmıştır. Yapılan çalışmada ilk olarak giriş kısmı yer almaktadır. Burada çalışmanın amacı ve metodu verilmiştir. Ardından yapılan çalışmaya ışık tutmak için teorik çerçeve yer almaktadır. Burada, kamusal açık alanlar başlığı altında sokak tipolojileri ve çıkmaz sokaklar hakkında bilgi aktarılmaktadır. Üçüncü bölümde ise alan çalışmasının değerlendirmesi yapılmıştır. Ardından, mimari ve kentsel ölçekler ile ortaya çıkan çalışmada elde edilen özgün ve objektif bulgular ileriki çalışmalara veri oluşturacaktır. Bu çalışmadaki ana bulgular Gazimağusa suriçindeki birçok çıkmaz sokağın fiziksel ve fonksiyonel açıdan zayıf olduğunu göstermektedir. Anahtar Kelimeler: Gazimağusa Suriçi, Kentsel Tasarım, Sokak Tipolojisi, Çıkmaz Sokak, Görsel Boyut, Fiziksel Boyut, Fonksiyonel Boyut, Sosyal Boyut, Morfolojik Boyut, Algısal Boyut
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2016. Supervisor: Assoc. Prof. Dr. Mukaddes Faslı.
Keywords: Architecture; Historic buildings - Sustainability - Conservation and restoration - Famagusta (Cyprus, North); Historic Urban Quarters - Revitalization - Famagusta (Cyprus, North); Historic Buildings - Preservation and Re - Use; Cul-de-sac (Dead End Street); Functional Dimension; Morphological Dimension; Urban Design; Perceptual Dimension; Physical Dimension; Social Dimension; Street Typology; Visual Dimension; Walled City of Famagusta